Basic Psychological Needs in Childhood and Adolescence - Michael Borg-Laufs (Journal of Education and Research, 2013)
In this article, four basic psychological needs, derived from psychological basic research, are presented. These are the needs for orientation and control, pleasure gain/distress avoidance, self esteem protection, and attachment. It is argued, that the satisfaction or violation of these needs has a main impact on the development of children and adolescents. To take these needs into account in various areas of pedagogical and psychosocial work gives good opportunities to help children and adolescents developing in a desired direction. The use of this concept is helpful in western societies as well as in developing countries.